Pengaruh Penerapan Metode Quantum Kauny terhadap Peningkatan Kemampuan Tahfidz Qur’an Siswa di SD IT Cendekia Darussalam - Afriandi, Dicki; Salami, Salami; Huwaida, Huwaida (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2024)
Problems that become obstacles in carrying out the tahfidz Qur'an program at SD IT Cendekia Darussalam, thereby disrupting the improvement of the quality and ability of tahfidz Qur'an of students at school, include the lack of enthusiasm and motivation of students in memorizing the Qur'an, the deposit for memorizing was not fluent, students could not understand the meaning of their memorization and also the use of learning media and the choice of methods were inappropriate which cause the problems with the quality of students' memorization.This study was aimed to find out (a) how high the quality of students' memorization of the Qur'an is after implementing the quantum kauny method at SD IT Cendekia Darussalam. (b) the effect of applying the quantum kauny method on improving students' tahfidz Qur'an abilities at SD IT Cendekia Darussalam. The method used in this research was quantitative experimental method with a Quasi Experimental pretest posttest control group design. The samples in this study were students of class VI AL-Munadi and class VI Al-Munawwir. Data collection techniques in this research consisted of tests, documentation, observation and interviews. The results of the research show that there is a difference in test results using the Quantum Kauny method in pretest and posttest using the conventional method, this is proven by the